Reading mediation from a discursive semiotic perspective: Guiding questions from the story análisis El tigre y el ratón, de Keiko Kasza - Rojas Gamboa, Yuly Andrea (Rastros Rostros, 2020)
Purpose: This article proposes a reading mediation exercise based on the discursive semiotic analysis of a story. Description: In this sense, the teacher is offered a series of inferential questions as a didactic possibility to guide the interpretation of the discursive manipulation carried out by the actors in the story El tigre y el ratón, by Keiko Kasza. Point of view: Various forms of manipulation are configured in the story: seduction, temptation and intimidation. It is relevant for didactics, teaching reading through various inferential type questions with which the student can identify and understand the operation of these forms of manipulation. Conclusion: Finally, reading mediation from a semiotic-discursive position develops critical reading processes that enable the construction of meaning and the creation of possible worlds for readers.